Kreatifitas Guru dalam Mengembangkan Modul Pembelajaran Materi Aqidah Akhlak Model Majalah Anak untuk Siswa Madrasah Ibtidaiyah - Sobirin, Ahmad Muhajir (Institut Agama Islam Sunan Giri Ponorogo, 2023)
One of the aims of this study was to create the Aqidah Akhlak module as a model for a children's magazine to meet the needs of Aqidah Akhlak educational resources at Mujahidin Islamic elementary schools. This is very important because the teacher's role is not only to teach but also to help. This study uses the Borg and Gall development model. There are seven stages used, namely product planning, product development, initial product design, field trials, product revision, and final results. The Aqidah Akhlak module, a children's magazine model for class IV MI, was made after going through various processes. After testing the experts, the product resulting from this development has been declared valid. Percentage of results: Material expert validation was 90%, design expert validation was 89.3%, and supporting teacher validation was 91%. The results of the field trials showed that the children's magazine model Aqidah Akhlak module was effective, because the posttest scores showed an increase in the average student learning outcomes from before. Furthermore, after calculating with the N-Gain formula, a value of 0.3 is obtained, which indicates that the level of effectiveness of the product resulting from the development is in the